Complicated colonic intussusception - Justin James; Paul N Strauss (Journal of Emergencies, Trauma and Shock, 2012)
The manuscript deals with the case of a 53-year-old woman who developed large bowel obstruction. Per-rectal examination revealed a pedunculated lesion in the rectum; rigid sigmoidoscopy revealed a prolapsing pedunculated mass with a necrotic surface. The patient recovered well following anterior resection. Histology confirmed a pedunculated sub mucosal lipoma as the lead point for intussusception. Colonic intussusception is a rare cause of adult large bowel obstruction, and the preoperative clinical diagnosis of this condition can be difficult. Resection of the involved segment of the colon is the most appropriate choice of treatment in most such cases.